Influenza as a Measure of Maternal Immune Activation and Its Effects on the Incidence of Encephalocele and Microtia. (March 2021) - Momin, Arsh; Grogan, Dayton; Carroll, William; Linder, Daniel; Yu, Jack C.
Objective: Activation of the maternal immune (MIA) system while pregnant can have significant effects on fetal development. Here, the authors sought to examine MIA and its effects on fetal craniofacial formation. As a measure of MIA, data on maternal influenza infection was used, as influenza occurs in a predictive fashion, is not vertically transmitted, and is found to generate a robust maternal immune response. Thus, this study measures the association of the incidence of influenza infection in the United States with the incidence of craniofacial congenital deficits—specifically encephalocele and microtia.Methods: The National Inpatient Sample Database (NIS) was referenced to identify national estimates of infants born with each disease from 2004 to 2013. The gross monthly disease incidences were adjusted based on the number of newborns each month. The National Respiratory and Enteric Virus Surveillance System's FluView database from the CDC was used to obtain influenza data from 2003 to 2013. Mixed effect logistic regression analyses were conducted to find the association between influenza occurrence and each disease, specifically an odds ratio (OR).Results: There were 2858 infants born with encephalocele and 3371 born with microtia from January 2004 to December 2013. Microtia showed no statistically significant correlation with influenza rates and served as a methodologic control. Encephalocele, however, showed a strong correlation with influenza infection specifically during the eighth month of pregnancy (OR = 34.538, 95% confidence interval: 3.815-312.681).Conclusion: This study shows a strong correlation between maternal influenza infection during the eighth month of pregnancy and encephalocele incidence. This suggests that there is an additional trigger for encephalocele development towards the end of the pregnancy not currently understood in the literature. Although there appears to be a connection between MIA and encephalocele formation, more research is needed to confirm this theory.